2021
DOI: 10.1101/2021.02.03.429623
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Glutamatergic dysfunction precedes neuron loss in cerebral organoids withMAPTmutation

Abstract: Frontotemporal dementia (FTD) due to MAPT mutation causes pathological accumulation of tau and glutamatergic cortical neuronal death by unknown mechanisms. We used human induced pluripotent stem cell (iPSC)-derived cerebral organoids expressing tau-V337M and isogenic corrected controls to discover early alterations due to the mutation that precede neurodegeneration. At 2 months, mutant organoids show upregulated expression of MAPT, and glutamatergic signaling pathways and regulators including the RNA-binding p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 104 publications
(145 reference statements)
0
8
0
Order By: Relevance
“…Human oTau seeding in hiNCs before combination with hiACs allows for a discrete analysis of how neuronal tau pathology develops and interacts with neighboring astrocytes in a physiologically relevant spatial context. This targeted and controlled methodology allows for a deeper level of study of tau induced phenotypes in vitro beyond that previously shown [28][29][30]32,33,83,84 . Previous studies with microfluidic and organoid models have developed some phenotypes of interest such as tau hyperphosphorylation and neurodegeneration in glutamate toxicity challenged MAPT mutant iPSCs 83 , 29 .…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Human oTau seeding in hiNCs before combination with hiACs allows for a discrete analysis of how neuronal tau pathology develops and interacts with neighboring astrocytes in a physiologically relevant spatial context. This targeted and controlled methodology allows for a deeper level of study of tau induced phenotypes in vitro beyond that previously shown [28][29][30]32,33,83,84 . Previous studies with microfluidic and organoid models have developed some phenotypes of interest such as tau hyperphosphorylation and neurodegeneration in glutamate toxicity challenged MAPT mutant iPSCs 83 , 29 .…”
Section: Discussionmentioning
confidence: 98%
“…The AstTau system allows for a detailed analysis of astrocytic phenotypes that are associated with tau pathology in a manner not easily studied with in vivo models that take 6-8 months to develop glial populations 29, 77 . The incorporation of hiACs in the AstTau model is necessary for neuronal survival in 3D culture, while also enabling study of the evolution of the interaction over the disease course.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations